The Role of Interpersonal Communication in Personal Development and Lifelong Learning for Employees - Yul Windiya Rini; Mohammad Isa Anshori (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the role of interpersonal communication in individual development and lifelong learning. Literature study and bibliometric techniques were conducted to explore the roles of interpersonal communication, individual development, and lifelong learning. The results of the research show that interpersonal communication is important in the development of individual employees, both personal and professional. Effective interpersonal communication facilitates collaborative learning, improves communication skills, and forms strong working relationships. This research is expected to provide practical recommendations that can be used by organizations in improving communication to employees to achieve maximum organizational goals through employee development